EFEKTIVITAS PENYULUHAN KESEHATAN TENTANG ANEMIA TERHADAP PENGETAHUAN IBU HAMIL PASCA KRISIS KESEHATAN DI PUSKESMAS PANAMBUNGAN - Puspita, Winda Dwi; Purnamasari, Dian; W, Ikrawanty Ayu; AR, Putra Az-Zahra (JURNAL KESEHATAN DELIMA PELAMONIA, 2025)
Background Anemia in pregnant women is strongly related to mortality and morbidity in mothers and babies, including the risk of miscarriage, stillbirth, prematurity, and low birth weight. The purpose of the study is to determine the effectiveness of health counseling and increase the knowledge of pregnant women about anemia in pregnancy. Methods This study uses quantitative research with the "One Group Pretest-Posttest Design" method, obtained from primary data using the "Pretest and Posttest" questionnaire. The results of the research in this study showed that there was an increase in knowledge as much as (15.2%) from the results of the post test while the results of the pre test amounted to (5.8%). Conclusion of providing health counseling on increasing pregnant women's knowledge about anemia in pregnancy. The suggestion in the study is that it is expected for future researchers to be able to develop or explore other factors related to anemia in pregnancy..